Relevansi Gaya Kepemimpinan Transformasional B.J. Habibie terhadap Tantangan Inovasi Nasional di Era Modern Indonesia - Ririn Deswita Putri; Nabila N; Bagas Saputra; Nabila Wandarizqa; Melati M; Risma Nursuhayla; Edy Akhyary (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Transformational Leadership is a leadership style that inspires, motivates employees to work creatively and innovatively and adapt to change. The situation created brought about administrative reform that relies on the ability to think in making the right decisions in maintaining a country's stability, in addition to a vision and mission dedicated to creating significant changes in the post-New Order era by voicing press freedom to realize good governance through transparency and government accountability. This study uses a literature study method that analyzes previous research on the importance of transformational leadership styles today, relevantly providing answers that motivating leaders can increase employee innovative behavior in advancing the company by collecting objective data through current topics. The purpose of the study was to analyze the relevance of BJ Habibie's leadership style to today's leadership in facing the challenges of modern innovation. Therefore, transformational leadership has an important role in public organizations understanding the actors involved in thinking openly in understanding changes in modern organizations.Â